2010
DOI: 10.1128/aac.00010-10
|View full text |Cite
|
Sign up to set email alerts
|

Striking Species Difference in the Contribution of Concentrative Nucleoside Transporter 2 to Nucleoside Uptake between Mouse and Rat Hepatocytes

Abstract: Concentrative nucleoside transporter 2 (CNT2) (encoded by the SLC28A2 gene) transports various antiviral or antitumor purine nucleoside analogs to be involved in their pharmacokinetics and pharmacological actions. The results of our study showed that mouse hepatocytes hardly expressed CNT2 mRNA and no CNT2-dependent nucleoside uptake was observed, while rat hepatocytes exhibited high CNT2-dependent nucleoside uptake activity levels with abundant CNT2 mRNA expression. We concluded that CNT2 contributes consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Such data are comparatively unavailable in the academic literature, and we strongly encourage their publication so that people can see the extent of the inter-species variation of drug uptake into particular organs or tissues, which variation can again be considerable (e.g., Shilling et al, 2006 ; Shitara et al, 2006 ; Li et al, 2008 ; Furihata et al, 2010 ; Chu et al, 2013a ; Grime and Paine, 2013 ; Musther et al, 2014 ).…”
Section: We Propose Some Candidate Discriminating Experiments That Admentioning
confidence: 99%
“…Such data are comparatively unavailable in the academic literature, and we strongly encourage their publication so that people can see the extent of the inter-species variation of drug uptake into particular organs or tissues, which variation can again be considerable (e.g., Shilling et al, 2006 ; Shitara et al, 2006 ; Li et al, 2008 ; Furihata et al, 2010 ; Chu et al, 2013a ; Grime and Paine, 2013 ; Musther et al, 2014 ).…”
Section: We Propose Some Candidate Discriminating Experiments That Admentioning
confidence: 99%
“…However, whether and how the increase of CD157 involved in the function of cardiac Tregs post MI need further exploration. CNT2, a high-affinity adenosine transporter mediating salvage of nucleoside, modulation of purinergic signaling, and energy metabolism in intestinal and liver parenchymal cells, also exhibited a marked elevation in cardiac Tregs at day 7 post-MI 39 - 41 . Borg et al reported no difference in Cnt2 expression in CD4 + T-cells from blood and heart 3 days after I/R injury 23 , but our results suggested that CNT2 may also exert its function in injured hearts by regulating purinergic signaling on T cells post-MI.…”
Section: Discussionmentioning
confidence: 99%
“…Uridine is also a substrate for ENT3, but the intracellular location of this transporter discards any role in initial cellular uptake of uridine [12], whereas ENT4 fails to transport uridine [9]. To discriminate among CNT and ENT activities, we used the differential sensitivity of these transporters to sodium withdrawal and to inhibitors such as NBMPR (which inhibits ENT1 when used at 100 nM and ENT1 and ENT2 when used at 100 µM, but not CNTs) [30], thymidine (blocking CNT1 and CNT3) [19] and inosine (blocking CNT2 and CNT3) [31] (Table 1).…”
Section: Methodsmentioning
confidence: 99%